Numerical Study of Air Distribution Inside Exhibition Hall - Rujipanich, Supasin; Khaothong, Kunthakorn (Srinakharinwirot University Engineering Journal, 2025)
Currently, the distribution of air through duct systems in large buildings commonly uses galvanized steel sheet ducts, which deliver air into the conditioned space using air diffusers. However, it has been observed that galvanized steel sheet ducts are expensive, difficult to install, and experience air pressure within the ducts during air delivery. Furthermore, using air diffusers does not provide uniform air distribution across the conditioned space, as the air diffusers can only deliver air to specific spots, leading to areas with insufficient airflow. As a result, the modern alternative is the use of polyester fabric ducts coated with PVC acrylic. These ducts distribute air through permeation or through holes in the duct, allowing air to be spread evenly across the conditioned space. This offers a potential design solution. This research presents an air distribution model using polyester fabric ducts coated with PVC acrylic, using a case study of an exhibition building with an air conditioning system. The study applies computational fluid dynamics to simulate the air distribution through three types of perforated ducts: air distribution through holes of fixed size (with no heat load), air distribution through porous holes (with no heat load), and air distribution through porous holes along the entire length of the duct (with heat load).The results indicate that the polyester fabric duct coated with PVC acrylic, in the third configuration (Model C) (air distribution through porous holes along the entire duct length, with heat load), is the most effective in delivering air and maintaining temperature when compared to the other configurations.